Action and Object Word Writing in a Case of Bilingual Aphasia - Kambanaros, Maria; Messinis, Lambros; Anyfantis, Emmanouil (My University, 2012)
We report the spoken and written naming of a bilingual speaker with aphasia in two languages that differ in morphological complexity, orthographic transparency and script Greek and English. AA presented with difficulties in spoken picture naming together with preserved written picture naming for action words in Greek. In English, AA showed similar performance across both tasks for action and object words, i.e. difficulties retrieving action and object names for both spoken and written naming. Our findings support the hypothesis that cognitive processes used for spoken and written naming are independent components of the language system and can be selectively impaired after brain injury. In the case of bilingual speakers, such processes impact on both languages. We conclude grammatical category is an organizing principle in bilingual dysgraphia.
Keywords: Lexical access; Dysgraphia; Orthographic Autonomy Hypothesis (OAH); Greek